The kinetic behavior of matrine in pig intestinal lumen after oral administration and its physiologically based pharmacokinetic modeling - Yang, Bo; Jia, YiWei; Wang, FuHao; Lv, XiaoLing; Ma, SuYang; Tan, YaXin; Zhang, WanXin; Wan, Dan; Li, Rui; Zhou, DanNa; Yu, DaoJin (Frontiers in Veterinary Science, 2025)
IntroductionMatrine (MT) has been found to restore the susceptibility of Escherichia coli to a variety of antibiotics in vitro. Nevertheless, the absence of pharmacokinetic data makes it uncertain whether MT exhibits efficacy in vivo. The study aimed to investigate the kinetic behavior of MT in pig intestinal lumen, the primary site for the colonization of enterotoxigenic Escherichia coli, and to develop a minimal physiologically based pharmacokinetic (PBPK) model for MT in pig intestinal lumen.MethodsTwo animal experiments were carried out for these purposes. In experiment 1, 12 pigs were implanted with a sterile T-cannula, and then were given a single oral dose of MT or MT-Amoxicillin (AMO) combination at 40 or 70 mg/kg. In experiment 2, 25 pigs were administered with MT at 50 mg/kg/d by oral gavage for 5 d. Intestinal contents were collected at predetermined times and analysed by liquid chromatography tandem mass spectrometry (LC–MS/MS) method. The concentration-time data were analysed by non-compartmental method. Subsequently, a four-compartment PBPK model was developed and validated.ResultsAfter oral administrations, the MT concentrations in pig intestinal lumen increased rapidly and reached their peaks within 2 h, then decreased in a two-phase decay pattern. The co-administered AMO did not alter the kinetic behavior of MT in pig intestinal lumen. The PBPK model gave an accurate prediction of MT concentrations in pig intestinal lumen at most time points.DiscussionA dosage regimen of 70 mg/kg every 8 h was recommended to ensure a sufficient drug exposure.